THE STAGES OF ENGLISH LANGUAGE ACQUISITION: A COMPREHENSIVE ANALYSIS OF LEARNING PROFICIENCY - Tojiyeva Marxabo Akbarovna, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article explores the systematic progression of English language learning, categorized  into  distinct  development  stages.  Based  on  contemporary  cognitive linguistics and Second Language Acquisition (SLA) theories, the study evaluates how learners  transition  from  total  beginners  to  fluent,  proficient  speakers.  The  analysis investigates the phonetic, morphological, and syntactic adjustments that occur at each level—ranging from pre-production to advanced fluency. Additionally, it highlights key psychological factors, pedagogical practices, and environmental conditions that optimize transition rates between these stages. This framework serves as a guide for curriculum  designers  and  educators  to  implement  scaffolded  teaching  methods adjusted to learners' developmental needs.